Pemodelan 3D pada Stabilitas Lereng Menggunakan Perkuatan Bronjong dengan Plaxis 3D Berbasis Elemen Hingga - Hamdhan, Indra Noer; Eliza, Emilia (Department of Civil Engineering, Diponegoro University, 2023)
The slope is a surface that lies at an angle to the horizontal. If the driving force at the slope is bigger than the resisting force, it can inflict a landslide. Gabions are one of the slope reinforcements structures that can be used to prevent landslides. Gabion has woven wire and has tensile strength. This study aims to examine the effect of modeling of tensile strength on gabion wire using Plaxis 3D, as well as the effectiveness of variations in height, variations in tensile strength, variations in gabion reinforcement patterns on slopes. The soil is modeled as homogeneous loamy sand with a geometry of 10m high and 1:1 slope. Modeling the tensile strength of gabions can increase the value of the safety factor by 9.5% compared to without modeling the tensile strength of gabions. The optimal gabion height that increasing the safety factor is 6m. The value of the tensile strength of gabion wire does not have a significant effect on the safety factor of the slope. The placement of gabions with a zigzag and lined pattern and a gentle slope will more increase the safety factor.